Hubungan Motivasi Peserta Ekstrakurikuler Terhadap Hasil Belajar PJOK SMA - Dewi Calista Fatimatuz Zahroh; Usman Wahyudi; Rama Kurniawan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
At SMA Laboratory UM and SMA Negeri 8 Malang, they have won various achievements in basketball. However, the level of motivation possessed by basketball extracurricular participants on PJOK learning outcomes is unknown. The purpose of this study was to determine the level of extrinsic and intrinsic motivation of male participants in participating in extracurricular activities at SMA Laboratory UM and SMA Negeri 8 Malang. In this study using quantitative descriptive, with a questionnaire survey. The population in this study was male basketball extracurricular participants at Laboratory High School UM 30 participants and SMA 8 Negeri Malang totaling 15 participants. The results of the analysis of motivational data on PJOK learning outcomes from Laboratory High School get coefficient of 0.520 is strong category, so that there is a strong relationship between motivation and PJOK learning outcomes. From the results of the analysis of motivational data on PJOK learning outcomes at SMA Negeri 8 Malang, the coefficient results were 0.820, a very strong category.